"Abraham's Bosom" (Luke 16:22-23) as a Key Metaphor in the Overall Composition of the Parable of the Rich Man and Lazarus - Somov, Alexey; Voinov, Vitaly 1975- (2017)
This article investigates the function of the metaphor "Abraham's bosom" (...) in Luke 16:22-23 using tools borrowed from cognitive linguistics, specifically Cognitive Metaphor Theory and Conceptual Blending Theory. We argue that the semantic components of "being in the place of honor at a feast" are essential to a proper understanding of this metaphor in the context of the parable and should be reflected in translations of this passage.
Keywords: Abraham -- Biblische Person; Reicher Mann und armer Lazarus; Metapher; Abraham's bosom; Bible. Luke; Bible. New Testament -- Criticism -- interpretation -- etc; Cognitive Linguistics; Cognitive Metaphor Theory; Conceptual Blending Theory; image schema; Linguistics; Luke; Metaphor in the Bible; Parable; RICH Man & Lazarus (Parable); Rich Man and Lazarus